2008
DOI: 10.1590/s0100-204x2008000800013
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética do umbuzeiro no Semi-Árido brasileiro, por meio de marcadores AFLP

Abstract: Resumo -O objetivo deste trabalho foi avaliar a distribuição da variabilidade genética do umbuzeiro (Spondias tuberosa), no Semi-Árido brasileiro, por meio de marcadores AFLP, para subsidiar estratégias de prospecção e conservação da espécie. Foram analisados 68 indivíduos de umbuzeiro de 15 ecorregiões, pelo dendrograma UPGMA e pela dispersão em escala multidimensional (MDS), com o coefi ciente de Jaccard de 141 bandas polimórfi cas de AFLP. A análise da variância molecular foi realizada pela decomposição tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
6
6
0
8
Order By: Relevance
“…The PCs produced the following numbers of polymorphic bands: ACT/CAT (13), AAG/CAT (9), AGC/CAC (12), AAG/CTC (12), ACA/CAT (14), AGG/ CTC (7), ACC/CTC (10), ACC/CCC (9), ACT/CTG (10), AAC/CTC (8), AGG/CAT (7), AAG/CAA (13), ACA/CTC (10), AAG/CTA (6), ACA/CCC (5), ACT/CAA (9), and AAC/ CTT (10). The mean of 9.6 differents polymorphic markers/ PC was lower than that reported by Vos et al (1995) and close to the mean of 10 polymorphic AFLP fragments reported by Santos et al (2008), who used silver-nitrate staining for umbu tree, under the same experimental conditions. Means of 1.4 and 7 monomorphic and polymorphic AFLP bands, respectively, were reported by Sun et al (2008), who used silver-nitrate staining, in J. curcas accessions in China.…”
Section: Resultssupporting
confidence: 73%
“…The PCs produced the following numbers of polymorphic bands: ACT/CAT (13), AAG/CAT (9), AGC/CAC (12), AAG/CTC (12), ACA/CAT (14), AGG/ CTC (7), ACC/CTC (10), ACC/CCC (9), ACT/CTG (10), AAC/CTC (8), AGG/CAT (7), AAG/CAA (13), ACA/CTC (10), AAG/CTA (6), ACA/CCC (5), ACT/CAA (9), and AAC/ CTT (10). The mean of 9.6 differents polymorphic markers/ PC was lower than that reported by Vos et al (1995) and close to the mean of 10 polymorphic AFLP fragments reported by Santos et al (2008), who used silver-nitrate staining for umbu tree, under the same experimental conditions. Means of 1.4 and 7 monomorphic and polymorphic AFLP bands, respectively, were reported by Sun et al (2008), who used silver-nitrate staining, in J. curcas accessions in China.…”
Section: Resultssupporting
confidence: 73%
“…Santos et al (2008), analyzing the genetic variability of the umbu fruit tree in a semi-arid area of Brazil, with an average of 14.2 bands per primer combination, obtained 141 and 58 polymorphic and monomorphic bands, respectively, using AFLP and 14 combinations of EcoR1/Mse1 primers (IC). A study of genetic diversity among sweet orange and Murcott tangor hybrids showed that of the 64 oligonucleotide primers used for fAFLP analysis, only 59 led to amplification results considered to provide enough resolution, originating 416 bands (Bastianel et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Características como maior tamanho de fruto, maior rendimento de polpa, redução do tamanho do caroço, dentre outras, são desejadas no melhoramento e é verificada grande variabilidade para esses caracteres (SANTOS, 1997;COSTA, et al, 2004;DUQUE, 2004;SANTOS et al, 2008). Assim, o objetivo desse trabalho foi caracterizar a variabilidade fenotípica existente entre os acessos de umbuzeiro, com base em dados quantitativos de frutos, visando aproveitá-la em futuro programa de melhoramento da espécie.…”
Section: Introductionunclassified